Clinical-epidemiological characteristics of the west nile fever in the Zaporizhzhia region - Ganta, V.; Onishchenko, T.; Оніщенко, Тетяна Євгенівна (Запорізький державний медичний університет, 2019)
The increased incidence of West Nile virus (WNV) fever in the European Union is associated with the global warming and an increase in the activity of natural foci of arbovirus infections associated with the natural migration of birds and population of commensal ornithocophilous mosquitoes, ticks. It was registered 86 cases of WNV fever in Ukraine, 40 cases (46.5%) of which were in Zaporizhzhya region during 2007- 2016. The purpose – to analyze the cases of the WNV disease in the Zaporizhzhya region. We studied case histories of 40 patients with diagnosis "West Nile fever", analyzated the results of clinical and serologic investigated. Most patients were hospitalized in May, August, September; 18 (75%) patients lived in rural areas, regularly went on nature trips and in anamnesis pointed to the mosquito bites. The IgG avidity index in 26 patients of the I group was determined in 10,7-25,3% and were registered next forms of the disease: meningeal 15 (57,7%), flu-like 7 (27%), mixed meningeal and exanthemous 4 (15,3%) with predominance moderate course of the diseases - 21 (80,8%) patients.
Keywords: тези доповідей